FRI0222 Impact of a Multidisciplinary Approach in Enteropathic Spondiloarthritis: Usefulness of a Combined Assessment in Prevalence, Characteristics, Diagnostic Delay and Outcomes. (9th June 2015) - Chimenti, M.S.; Conigliaro, P.; Ascolani, M.; Ballanti, E.; Onali, S.; Triggianese, P.; Collalti, G.; Calabrese, E.; Petruzziello, C.; Pallone, F.; Biancone, L.; Perricone, R.
Abstract : Background: Prevalence of Enteropathic-related Spondyloarthritis (SpAe) in inflammatory bowel disease (IBD) shows marked variations (18-45%) and may be underestimated by gastroenterologists. Objectives: In a prospective study, in a combined GastroIntestinal and RHeumAtologic "GiRha" clinic of the University of Rome "Tor Vergata", prevalence and characteristics of joint manifestations in inflammatory bowel disease (IBD) patients were evaluated. diagnostic delay and therapeutic modifications were also assessed. Methods: The study prospectively enrolled patients affected by IBD who presented muscolo-skeletal pain between November 2012 and July 2014. Disease activity in SpA patients was assessed using the ASDAS-CRP, BASDAI, BASFI, DAS44-CRP and HAQ-S. Results: SpAe was detected in 101 patients. In 65 cases this was a new diagnosis. Other rheumatologic diagnosis were: Osteoarthritis (30.3%), Fybromialgia (6.9%), Psoriatic Arthritis (4.3%), Rheumatoid Arthritis (3.2%) and Gout (1.6%). Prevalence of other extraintestinal manifestations (psoriasis, uveitis, primary sclerosing cholangitis and erythema nodosum) resulted higher in SpAe patients than that in IBD non-SpAe patients (p=0.04). 56.4% SpAe patients showed a high disease activity (ASDAS ≥2.1). 22.8% had axial involvement, peripheral involvement in 57.4% and a combination of peripheral and axial involvement in 19.8% of cases. Axial SpAe patients were preferentially male and showed increased ESR and CRP levels compared with peripheral SpAe patients. Peripheral SpAe patients showed higher DAS levels compared with that in both axial and axial+peripheral SpAe patients. The diagnostic delay (time between the onset of joint symptoms and first rheumatological encounter) was calculated for all SpAe patients. Patients with disease onset between 2000-2009 had a reduced diagnostic delay compared with those with joint onset in 1980-1989 and 1990-1999. The diagnostic delay was further reduced for those patients with joint onset after 2010 (Figure 1 ). A higher percentage of IBD patients were treated with disease-modifying anti-rheumatic drugs (p=0.04), anti-COX2 (p<0.0001) and anti-TNF drugs (p=0.001) after the rheumatological assessment. Clinical outcome demonstrate improuvement of disease activity after 6 months of combined aproach: ASDAS and DAS changed from 2.8±0.9 at baseline to 1.4±0.5 and 2.5±0.8 at baseline to 1.8±0.8 respectively. Conclusions: Multidisciplinary care facilitates the diagnosis and the management of rheumatic disorders in IBD offering a comprehensive treatment approach. Disclosure of Interest: None declared